2017
DOI: 10.1098/rsif.2016.0764
|View full text |Cite
|
Sign up to set email alerts
|

Frogs use a viscoelastic tongue and non-Newtonian saliva to catch prey

Abstract: Frogs can capture insects, mice and even birds using only their tongue, with a speed and versatility unmatched in the world of synthetic materials. How can the frog tongue be so sticky? In this combined experimental and theoretical study, we perform a series of high-speed films, material tests on the tongue, and rheological tests of the frog saliva. We show that the tongue's unique stickiness results from a combination of a soft, viscoelastic tongue coupled with non-Newtonian saliva. The tongue acts like a car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…The Stefan equation is only valid when the saliva layer is thin, the fluid is an incompressible Newtonian fluid and the flat plates are rigidthe last two assumptions do not hold for frog tongues. Nevertheless, in earlier work (Noel et al, 2017), we showed that Eqn 12 still gives a good estimate for the pull-off force of a plate from a frog tongue.…”
Section: How Viscous Saliva Enhances Adhesionmentioning
confidence: 77%
See 4 more Smart Citations
“…The Stefan equation is only valid when the saliva layer is thin, the fluid is an incompressible Newtonian fluid and the flat plates are rigidthe last two assumptions do not hold for frog tongues. Nevertheless, in earlier work (Noel et al, 2017), we showed that Eqn 12 still gives a good estimate for the pull-off force of a plate from a frog tongue.…”
Section: How Viscous Saliva Enhances Adhesionmentioning
confidence: 77%
“…muscle activation from the arm's base to tip, likely to overcome the large drag forces in the water (Yekutieli et al, 2005). In contrast, the frog tongue stretches passively during unraveling, with the ability to extend in length from 36 to 49 mm, a stretch percentage of 130% (Noel et al, 2017). Other papers have noted stretch percentages of 180% for inertial elongators such as Bufo marinus (Nishikawa, 1999;Nishikawa and Gans, 1996).…”
Section: Viscous Dissipationmentioning
confidence: 98%
See 3 more Smart Citations